SEMANTIC FORMULAS FOR GIVING COMPLIMENTS IN THE MACEDONIAN STANDARD LANGUAGE (Journal of Contemporary Philology, 2020)
This article aims to explore the syntactic structure of the most frequently used semantic formulas for expressing compliments during young population interactions, the most frequently used words in those formulas, and the topic they refer to. This approach presents a base to understand the similarities and thedifferences between the Macedonian and the other world languages, as well as the specific features of Macedonian. This qualitative research has a descriptive design, i.e., the corpus consists of 1000 semantic formulas collected through a survey in which 100 young people aged 18 – 22 in the Republic of N. Macedoniawere asked to list the compliments they use in their everyday interactions. The methods used are analysis, synthesis and comparison. The results indicate that in the Macedonian language the semantic formulas for giving compliments are the same as the formulas present in other foreign languages which have a simple sentence structure and that the Macedonian language features can be seen in the intensifiers and the possibility of combining them, as well as in the formulas that contain a noun group and a complex sentence structure.
Keywords: compliments; semantic formulas; syntactic structure; topic; Macedonian language